2021
DOI: 10.1186/s12902-021-00682-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Artesunate on cardiovascular complications in rats with type 1 diabetes mellitus

Abstract: Background The present study aimed to evaluate the effect of artesunate (ART) on the reduction of cardiovascular complications in a type 1 diabetes model and to investigate the associated mechanism based on the receptor for advanced glycation end-product (RAGE)/NF-κB signaling pathway. Methods A total of 40 male Sprague-Dawley rats were randomly divided into five groups: The healthy, diabetic, 50 mg/kg ART (ig) treatment diabetic, 100 mg/kg ART (ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Rats in ART-treated, Met-treated, and ART/Met co-treated diabetic groups were treated with ART alone (50 mg/kg; Guilin Pharmaceutical Co., Ltd., Guilin, China), Met alone (150 mg/kg; Shenzhen Neptune Pharmaceutical Co., Ltd., Shenzhen, China), and ART (50 mg/kg) combined with Met (150 mg/kg), respectively, whereas the non-diabetic control and untreated diabetic rats received equivalent doses of saline. Notably, the administered ART and Met doses were in accordance with previous studies ( Cai et al, 2018 ; Bradley et al, 2019 ; Inyang et al, 2019 ; Chen et al, 2021 ).…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…Rats in ART-treated, Met-treated, and ART/Met co-treated diabetic groups were treated with ART alone (50 mg/kg; Guilin Pharmaceutical Co., Ltd., Guilin, China), Met alone (150 mg/kg; Shenzhen Neptune Pharmaceutical Co., Ltd., Shenzhen, China), and ART (50 mg/kg) combined with Met (150 mg/kg), respectively, whereas the non-diabetic control and untreated diabetic rats received equivalent doses of saline. Notably, the administered ART and Met doses were in accordance with previous studies ( Cai et al, 2018 ; Bradley et al, 2019 ; Inyang et al, 2019 ; Chen et al, 2021 ).…”
Section: Methodssupporting
confidence: 72%
“…Importantly, ART is not only able to pass through the blood-brain barrier and maintain a high concentration in the brain ( Zhao and Song, 1989 ; Zuo et al, 2016 ), but is also able to adjust glucose homeostasis against diabetes and its complications ( Sun et al, 2018 ; Xu et al, 2019 ; Maurya et al, 2021 ). Moreover, our previous study also showed that ART controlled blood glucose levels and prevented cardiovascular complications in diabetic rats ( Chen et al, 2021 ). However, to date, no study has investigated effects of ART alone or in combination with Met against diabetic xerostomia and elucidated the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 87%
“…[38,39] ART can be used in the treatment of diabetes and diabetic complications, such as diabetic nephropathy, diabetic peripheral neuropathy and cardiovascular complications. [40–42] In addition, ART reduced retinal thickness in diabetic rats significantly and attenuated retinal inflammation in diabetic rats through AMPK/Sirt1-mediated autophagy. [43] Activation of adenosine 5’-monophosphate (AMP)-activated protein kinase (AMPK) can induce autophagy by directly suppressing the phosphorylation of the mechanistic target of rapamycin (mTOR).…”
Section: Resultsmentioning
confidence: 99%
“…Artesunate (ART, C 19 H 28 O 8 , molecular weight 384.42), a derivative of artemisinin, has been widely used in clinical practice orally and intravenously as a safe and effective antimalarial drug . Previous studies from our lab have revealed that ART plays important roles in immune status, anti-inflammation response, blood glucose, and inhibition of bone resorption . However, whether ART regulates the occurrence and development of DKD by regulating the level of autophagy remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Previous studies from our lab have revealed that ART plays important roles in immune status, 22 anti-inflammation response, blood glucose, 23 and inhibition of bone resorption. 24 However, whether ART regulates the occurrence and development of DKD by regulating the level of autophagy remains unknown. We established a rat model of diabetes with periodontitis to explore whether periodontitis could affect the progression of DKD through the dysbiosis of microbiota.…”
Section: Introductionmentioning
confidence: 99%